Prasiolales (Trebouxiophyceae, Chlorophyta) of the Svalbard Archipelago: diversity, biogeography and description of the new genera Prasionella and Prasionema. Issue 2 (2nd April 2016) - Heesch, Svenja; Pažoutová, Marie; Moniz, Mónica B.J.; Rindi, Fabio
Abstract: Species of Prasiolales (Trebouxiophyceae, Chlorophyta) are among the most common terrestrial and freshwater algae in polar regions. Comprehensive molecular studies of this group are available for Antarctica, but not yet for Arctic regions. We examined the diversity of the Prasiolales in the Svalbard Archipelago combining morphological observations of field-collected material, culture studies, molecular data (plastid rbc L and tuf A sequences) and literature records. We confirmed the widespread occurrence of Prasiola crispa and P. fluviatilis, species recorded from Spitsbergen since the 19th century. Molecular phylogenetic analyses led to the discovery of two new genera of Prasiolales. Prasionema payeri is morphologically identical to filamentous stages of P. crispa, but represents an early-diverging lineage in the order. Prasionella wendyae is a colonial alga reproducing by aplanospores; its phylogenetic position is among the basal lineages of the order, but it could not be reliably reconstructed due to weak statistical support. The inclusion of P. wendyae in the prasiolalean phylogeny determined the paraphyly of Rosenvingiella, requiring the establishment of the new genus Rosenvingiellopsis for R. constricta . A poorly known species described from Spitsbergen, Ulothrix discifera, is transferred here to Rosenvingiella . Whereas some species of Prasiolales have bipolar distribution ( P. crispa ), others appear to be restricted to one or other of the poles. Our results suggest that polar regions are still a major repository of unknown algal diversity and highlight the importance of continued field surveys and the use of molecular data.